The Search for a Government System in Turkey: The Presidentialism Debates between Democratization and the Quest for More Power - PAPUÇÇULAR, HAZAL (My University, 2020)
This article aims to analyze the various debates around the transformation of Turkey’s government system from parliamentarism to presidentialism. It argues that the current authoritarian nature of the Turkish politics is helpful to make sense of the way that these constitutional amendments of 2017 were made and accepted, and also of the content and the scope of the ‘Turkish type of presidentialism’. However, it also suggests that limiting the discussions to the late 2010s results in incomplete accounts. Thus, by arguing that a longer-term approach is needed to fully understand the government system change in Turkey, this article shows that the AKP’s demand for a presidential system actually dates back to the first decade of the century. Accordingly, the discourse regarding the system change shifted from clashing the tutelary aspects of the state towards efficiency and persistence in state affairs, reflecting the 21st century paradigms in Turkish politics that evolved from debates of democratization to the quest for more power.
Keywords: Presidentialism; Hyper-presidentialism; Parliamentarism; Turkish type of presidentialism; AKP